2018
DOI: 10.1155/2018/6050234
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Ability of Superelastic and Controlled Memory Nickel-Titanium File Systems: An In Vitro Study

Abstract: Improvements in the thermomechanical processing procedures of NiTi wires have led to the development of new NiTi instruments that compose mainly of martensite crystals, making the wire stable at clinical condition. This study aimed at comparing the shaping ability of two rotary nickel-titanium systems manufactured from different NiTi wires. Twenty simulated root canals each with a curvature of 35° in resin blocks were divided into two groups of 10 canals each. Canals in the first group were prepared with super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…Due to this, they may continue to be in the austenite phase while being employed in a clinical setting, causing an uneven distribution of stress while recovering their form after instrumentation. The findings of this experiment agree with those of Ba-Hattab and Pahncke,[ 32 ] who investigated the shaping capability of the F360 file with different NiTi rotary file systems made from different metallurgy, and they found that the F360 file caused the root canal walls to be under inconsistent amounts of stress. In addition, the S-shaped cross-section of the F360 files may have put extra stress on the dentinal wall.…”
Section: Discussionsupporting
confidence: 88%
“…Due to this, they may continue to be in the austenite phase while being employed in a clinical setting, causing an uneven distribution of stress while recovering their form after instrumentation. The findings of this experiment agree with those of Ba-Hattab and Pahncke,[ 32 ] who investigated the shaping capability of the F360 file with different NiTi rotary file systems made from different metallurgy, and they found that the F360 file caused the root canal walls to be under inconsistent amounts of stress. In addition, the S-shaped cross-section of the F360 files may have put extra stress on the dentinal wall.…”
Section: Discussionsupporting
confidence: 88%
“…e thermal treatment employed in manufacturing NiTi les enhances their mechanical properties [7]. However, the mechanical properties may be negatively or positively affected by heat generated during the sterilization process [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, a range of techniques were employed to assess canal's amount of transportaion, the remainder of remaining thickness of dentinal material, and centering ability. These included the utilization of radiographic methods (9) , the meticulous process of serial sectioning (19) , visual evaluations through photography (20) , intricate observations using scanning electron microscopy (21) , and the application of computer manipulation techniques (22) . However, these methods had inherent invasiveness and posed challenges in accurately repositioning specimens before and after instrumentation.…”
Section: Discussionmentioning
confidence: 99%